LOTS vs HOTS: Evaluation of History Textbooks for Class XII Senior High School - Najuah Najuah; Sari Madani Rangkuti; Ricu Sidiq; Pristi Suhendro Lukitoyo; Arfan Diansyah (STAI Hubbulwathan Duri, 2024)
This study evaluates the prevalence of Lower Order Thinking Skills (LOTS) and Higher Order Thinking Skills (HOTS) questions in Indonesian History textbooks for twelfth-grade students. Utilizing a quantitative research methodology, the study analyzes the first-semester evaluation questions from textbooks published by the Ministry of Education and Culture, Erlangga, and Grafindo. Employing descriptive statistical techniques, the analysis reveals distinct disparities in the balance of LOTS and HOTS questions. Specifically, the Erlangga textbook contains 82.6% LOTS and 17.4% HOTS questions, while the Grafindo textbook shows a distribution of 96.7% LOTS and 3.3% HOTS questions. Furthermore, a comparative assessment of descriptive questions shows that the Ministry of Education and Culture’s textbook exhibits a ratio of 38.9% LOTS to 61.2% HOTS, Erlangga has 73.4% LOTS to 26.6% HOTS, and Grafindo features 90% LOTS to 10% HOTS. The findings indicate a significant underrepresentation of HOTS-based questions in the analyzed textbooks, suggesting a potential gap in fostering higher-level cognitive skills among students.